ANALISIS PENDAPATAN DAN KELAYAKKAN USAHA ANEKA OLAHAN COKELAT PADA INDUSTRI RUMAH TANGGA CHOCO CRAFT DI KOTA PALU - wahyuni, Noni sri; Yantu, MR; Muis, Abdul (AGROTEKBIS, 2018)
This study aims to determine the income earned Craff chocolate industry in a variety of processed chocolate business and also to determine the feasibility Choco CraftIndustry in Palu . This study was conducted in February and March 2015. Respondent done intentionally ( purposive ) and respondents drawn amounted to 3 people, and two of those consumers who are expected to impart information that is accurate. The analysis used in this study is an analysis of earnings ( π ) and feasibility.The results showed that the total receipts ( R ) Rp . 5,030,000, while the total cost ( C ) of Rp.3,929,050 , so results of the analysis states that the income earned in Industry Choco Craft processed chocolate for Rp.1,100,950. The results of the analysis also shows that at each increase in the cost of Rp 1.00, - thus Revenue of Cost Ratio of various processed chocolate Industry Choco Craft gained by 1.2 thus a variety of processed chocolate at Choco Craft Industry is feasible to be running. Key Words: Feasibility, Processed chocolate, Revenues.